Study protocol of the European Urban Burden of Disease Project: a health impact assessment study. Issue 1 (20th January 2022) - Nieuwenhuijsen, Mark J; Barrera-Gómez, Jose; Basagaña, Xavier; Cirach, Marta; Daher, Carolyn; Pulido, Maria Foraster; Iungman, Tamara; Gasparrini, Antonio; Hoek, Gerard; de Hoogh, Kees; Khomenko, Sasha; Khreis, Haneen; et al.
Abstract : Introduction: Cities have long been known to be society's predominant engine of innovation and wealth creation, yet they are also hotspots of pollution and disease partly due to current urban and transport practices. The aim of the European Urban Burden of Disease project is to evaluate the health burden and its determinants related to current and future potential urban and transport planning practices and related exposures in European cities and make this evidence available for policy and decision making for healthy and sustainable futures. Methods and analysis: Drawing on an established comparative risk assessment methodology (ie, Urban and Transport Planning Health Impact Assessment) tool), in nearly 1000 European cities we will (1) quantify the health impacts of current urban and transport planning related exposures (eg, air pollution, noise, excess heat, lack of green space) (2) and evaluate the relationship between current levels of exposure, health impacts and city characteristics (eg, size, density, design, mobility) (3) rank and compare the cities based on exposure levels and the health impacts, (4) in a number of selected cities assess in-depth the linkages between urban and transport planning, environment, physical activity and health, and model the health impacts of alternative and realistic urban and transport planning scenarios, and, finally, (5) construct a healthy city index and set up an effective knowledge translation hub to generate impact in society and policy. Ethics and dissemination: All data to be used in the project are publicly available data and do not need ethics approval. We will request consent for personal data on opinions and views and create data agreements for those providing information on current and future urban and transport planning scenarios. For dissemination and to generate impact, we will create a knowledge translation hub with information tailored to various stakeholders.